Quantitative Chemical Proteomic Profiling of Ubiquitin Specific Proteases in Intact Cancer Cells - Ward,JA; McLellan,L; Stockley,M; Gibson,KR; Whitlock,GA; Knights,C; Harrigan,JA; Jacq,X; Tate,EW (ACS Chemical Biology, 2016)
Deubiquitinating enzymes play an important role in a plethora of therapeutically relevant processes and are emerging as pioneering drug targets. Herein, we present a novel probe, Ubiquitin Specific Protease (USP) inhibitor, alongside an alkyne-tagged activity-based probe analogue. Activity-based proteome profiling identified 12 USPs, including USP4, USP16, and USP33, as inhibitor targets using submicromolar probe concentrations. This represents the first intact cell activity-based profiling of deubiquitinating enzymes. Further analysis demonstrated functional inhibition of USP33 and identified a synergistic relationship in combination with ATR inhibition, consistent with USP4 inhibition.